PENERAPAN BIMBINGAN KLASIKAL DENGAN TEKNIK COOPERATIVE LEARNING TIPE SNOWBALL THROWING UNTUK MELATIH KEMAMPUAN BERPIKIR KRITIS SISWA KELAS XI - Sofiyah Asy Syarifatul Alifah; Mariatiningsih Mariatiningsih; Retno Tri Hariastuti; Sobi Mardiyas (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
Critical thinking is an intellectual process that involves the discovery, analysis, and evaluation of information obtained from observation and experience. This process is used to consider various options before making decisions or taking actions. By engaging in critical thinking, individuals thoroughly examine available information to ensure that the decisions made are the most appropriate and well-founded. Through these steps, the ability to analyze situations comprehensively and objectively can be enhanced, resulting in more planned and effective actions. This research aims to train the critical thinking skills of 11th-grade students using classical guidance services with the Cooperative Learning Technique of Snowball Throwing. This study is guidance counseling action research (PTBK), with data collection using a Likert scale and data analysis using the T-test. The results of the study indicate that classical guidance with the Cooperative Learning Technique of Snowball Throwing is capable of training the critical thinking skills of 11th-grade students at SMA Negeri 4 Jember.